On the results of N. P. Korneichuk obtained in 1990–1999 - Babenko, V. F.; Ligun, A. A.; Motornyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a brief survey of Korneichuk’s works published in 1990–1999.